Analysis of influencing factors of pneumatic flow enhancement of pumped concrete based on discrete element method - Su, Chang; Wu, Zhuang; Xu, Hua; Wang, Liu (Frontiers in Earth Science, 2022)
It is known that, long-distance concrete pipeline transportation often causes pipe blocking accidents. For the problem of pipeline blockage, we have invented a swirl speed-increasing device. In this study, the discrete element method was used to calibrate the parameters of the contact model through the slump bucket experiment, and a discrete element model of horizontal pumping concrete was established. Based on the particle unit, the flow-promoting mechanism of the swirl speed-increasing device was studied, and the effects of the pumping speed, the volume fraction of coarse aggregate and the wind speed output of the device on the movement state of the particles and the flow-promoting distance were analyzed. The results show that the maximum velocity and flow-promoting distance of the particle unit increase with the increase of pumping speed and wind speed, and decrease with the increase of the coarse aggregate volume fraction. When the pumping speed and wind speed are large, the installation distance of the flow promoting device should be increased. When the volume fraction of concrete aggregate is large, the installation distance of the flow promoting device should be shortened.